Penerapan Metode K-Nearest Neighbour Dalam Menentukan Kelayakan Calon Nasabah Yang Layak Untuk Kredit Mobil (Studi Kasus : Pt. Astra International,Tbk-Toyota) - Pratama, Tito Cakra (JURIKOM (Jurnal Riset Komputer), 2018)
In line with business growth, credit is an interesting issue to research. Some computer research to reduce the credit that has been done in order to avoid the collapse of a finance company and reduce errors in the process of determining the eligibility of prospective buyers to get credit in the purchase of cars. One of the failure factors in the credit business is the lack of accurate assessment of the ability of the debtor, resulting in mistakes in credit decisions that led to credit congestion.